Feeding practices and malnutrition at the Princess Marie Louise Children's hospital, Accra: what has changed after 80 years?. Issue 1 (December 2016) - Tette, Edem; Sifah, Eric; Tete-Donkor, Priscilla; Nuro-Ameyaw, Peter; Nartey, Edmund
Abstract Background Sub-optimal feeding practices are associated with malnutrition. In 1933, Dr Cecily Williams, while working at Princess Marie Louise Children's Hospital (PML) in Accra described Kwashiorkor as the disease of children "deposed" from breast feeding who were being fed plain fermented maize diets. Presently, it is not clear how this has changed after 80 years. Methods We conducted an unmatched case–control study at PML in 2013 in order to determine faulty feeding practices associated with malnutrition. PML is a 74 bed children's hospital and the largest centre for treating children with malnutrition in Ghana. Under-fives with Moderate or Severe Acute Malnutrition (SAM or MAM) were selected as cases while the controls were children without SAM or MAM. Results A total of 182 malnourished and 189 well-nourished under-fives and their mothers were studied. Faulty feeding practices including early weaning, shorter duration of exclusive breastfeeding, mixed feeding, bottle feeding and limited consumption of fruits were found. Though the use of "iced kenkey" a maize-based diet was limited, over one-third of malnourished children (39.1 %) were still being weaned with plain unfortified fermented maize gruel both of which Dr Williams associated with Kwashiorkor. Well-nourished children were more likely to receive solid food (38.0 %), fortified maize gruel (29.2 %), and Cerelac® (24 %) a processed cereal-based complementary food. A child's refusal to breastfeed was the most common reason for stopping breastfeeding among malnourished children. Conclusions More effective nutrition education and new complementary feeding diets that are wholesome yet appeal to a new generation of mothers are needed. The patho-physiology of feeding problems needs further study.